2014
DOI: 10.3857/roj.2014.32.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional conformal radiotherapy for portal vein tumor thrombosis alone in advanced hepatocellular carcinoma

Abstract: PurposeWe sought to evaluate the clinical outcomes of 3-dimensional conformal radiation therapy (3D-CRT) for portal vein tumor thrombosis (PVTT) alone in patients with advanced hepatocellular carcinoma.Materials and MethodsWe retrospectively analyzed data on 46 patients who received 3D-CRT for PVTT alone between June 2002 and December 2011. Response was evaluated following the Response Evaluation Criteria in Solid Tumors. Prognostic factors and 1-year survival rates were compared between responders and non-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Some studies reported response rates to prescribed BED [ 5 , 11 , 18 , 27 ]. Kim et al [ 5 ] reported that the response of PVT was higher if the prescribed BED was higher than 64 Gy 10 (50% vs. 0%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies reported response rates to prescribed BED [ 5 , 11 , 18 , 27 ]. Kim et al [ 5 ] reported that the response of PVT was higher if the prescribed BED was higher than 64 Gy 10 (50% vs. 0%).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 5 ] reported that the response of PVT was higher if the prescribed BED was higher than 64 Gy 10 (50% vs. 0%). Lee et al [ 18 ] reported that the response of PVT was higher if the prescribed BED was higher than 60 Gy 10 (26.1% vs. 6.5%). Another study by Kim et al [ 11 ] also reported that the response of PVT was higher if the prescribed BED was higher than 58 Gy 10 (54.6% vs. 20%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients who had large HCC mass with PVTT, we treated PVTT alone using TACE followed by RT. Because PVTT has limited applicability in TACE, it need to be treated with different modalities for better prognosis [ 10 ]. However, when the primary HCC was single, localized, close to PVTT, both HCC and PVTT lesions were included in GTV.…”
Section: Methodsmentioning
confidence: 99%